STUCTURE OF PULSED BED - I. A. Bokun (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2014)
The structure of pulsed layer is proposed which can be suggested as a state of particulates that is blown by intermittent gas flow with speed which has the force to start material moving. Layer during one cycle is in a suspension, falling down and immobile state resulting in changes of particles arrangement as well as ways of gas flowing through layer. Moreover, it allows carrying out effective interphase heat exchange even adamant real granulation.The process of formation of impact flows is considered aw well as their influence on formation of air bubbles in pulsed layer. At startup of air blast the balance between the force of hydro-dynamic resistance is broken, on one side, and forces of gravity, particles inertia and their links with walls on the other side. The layer is transferred in the state of pulsed pseudo-fluidization, and presents gas-disperse mixture, inside of which impulse of pressure increasing is spreading to all sides as pressure waves (compression). These waves are the sources of impact flows’ formation, the force of which is two times more than during the stationary flow.The waves of pressure are divided into weak and strong ones depending on movement velocity within gas-disperse system. Weak waves are moving with a sound speed and strong ones in active phase of pulsed layer are moving over the speed of sound limit within gas-disperse system. The peculiarity of strong wave is that parameters of system (pressure, density and others) are changing in discrete steps.The article describes the regime of layer’s falling down in the passive stage of cycle, which begins after finishing of gas impulse action. And suspension layer of moving up granular material is transferred in the state of falling resulting in change of the layer structure.